2018
DOI: 10.1016/j.jalz.2018.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Japanese and North American Alzheimer's Disease Neuroimaging Initiative studies: Harmonization for international trials

Abstract: These results support the feasibility of bridging of clinical trials in the prodromal stage of AD between Asia and western countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
110
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 95 publications
(115 citation statements)
references
References 26 publications
5
110
0
Order By: Relevance
“…Groups 2 and 3 had enough participants for statistical analyses, but female-dominant differences were observed in all groups. Total scores and subclassification domain items of the CogEvo, We also divided the total participants into three groups according to cut-off scores for the MMSE; that is, 24 and 26 points, which are commonly used to discriminate dementia from normal individuals, 2 and for registration criteria of the cognitively unimpaired (CU), 8,9 mild cognitive impairment (MCI) 10 and dementia (D) 11 in recent cohort studies, such as the Alzheimerʼs Disease Neuroimaging Initiative [12][13][14] and the Dominantly Inherited Alzheimer Network. 15 The numbers of participants, mean age, sex, and total and subclassified domain scores of CogEvo, MMSE scores and CDT scores are described in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Groups 2 and 3 had enough participants for statistical analyses, but female-dominant differences were observed in all groups. Total scores and subclassification domain items of the CogEvo, We also divided the total participants into three groups according to cut-off scores for the MMSE; that is, 24 and 26 points, which are commonly used to discriminate dementia from normal individuals, 2 and for registration criteria of the cognitively unimpaired (CU), 8,9 mild cognitive impairment (MCI) 10 and dementia (D) 11 in recent cohort studies, such as the Alzheimerʼs Disease Neuroimaging Initiative [12][13][14] and the Dominantly Inherited Alzheimer Network. 15 The numbers of participants, mean age, sex, and total and subclassified domain scores of CogEvo, MMSE scores and CDT scores are described in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…These findings suggest that the CogEvo test might also be feasible for preclinical observation studies or clinical trials for the prevention of dementia. In the MMSE, the range for the CU participants and participants with MCI was 24–30, and for mild Alzheimer's disease dementia the range was 20–26 . The CDR score and education duration‐dependent delayed recall score of the logical Memory II subscale for Wechsler Memory Scale‐Revised were additional criteria for discernment of CU, MCI and mild Alzheimer's disease dementia .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study protocol used in the J-ADNI has been described in detail elsewhere [3]. To describe the eligibility criteria briefly, CN participants in the J-ADNI were required to be 60 to 84 years of age, and have a physician's diagnosis of not having dementia or mild cognitive impairment, a CDR score of 0, and an MMSE score of 24 to 30 at the time of screening.…”
Section: Participants and Variables Analyzedmentioning
confidence: 99%
“…The Japanese Alzheimer's Disease Neuroimaging Initiative (J-ADNI) was the first large-scale longitudinal observational study in Japan, conducted between 2008 and 2014, following the North American ADNI (NA-ADNI), to elucidate the natural history of the early stages of AD in the Japanese population. We recently reported that individuals with mild cognitive impairment or mild AD exhibited similar profiles of cognitive and functional decline in the J-ADNI and the NA-ADNI [3]. The J-ADNI also included a 3-year follow-up with intensive assessments of 154 CN individuals from a total of 537 participants between 60 and 84 years of age.…”
Section: Introductionmentioning
confidence: 99%